Moldova : Education Sector Public Expenditure Review – Selected Issues - World Bank Group (World Bank, Washington, DC, 2018)
This report reviews selected issues in public expenditures for education in Moldova. It is the product not of a comprehensive analysis that would comprise a full-fledged Public Expenditure Review (PER), but from a review of key elements related to financing of the education sector as a whole, and to important sub-segments of the education and training system. In particular, after providing an overview of the governance and financing arrangements of the education system (chapter 1), and of recent general trends in education expenditures (chapter 2), the report focuses on trends in capital investment for pre-primary education, driven largely by the strong increases in the recent period (chapter 3). It then proceeds with a broad first assessment of the impact of ongoing optimization reforms in general education on efficiency, quality, and equity (chapter 4). The report also looks at the external efficiency of vocational education and training (VET) and higher education (HE), particularly on the extent to which financing mechanisms are applied to promote the demand-responsiveness of education and training provision.